PEMANFAATAN BUKU TEKS SEBAGAI SUMBER BELAJAR DALAM PEMBELAJARAN SOSIOLOGI KELAS XI SMAN 2 MENYUKE - Siska, Siska; Sulistyarini, Sulistyarini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to study textbooks in sociology as a source of learning textbooks can help as a source of learning and teaching sociology because there are materials, and various evaluations, looking for learning objectives can help optimally.The first choice of textbook criteria matches the relevance of the material contained in the textbook to the curriculum structure. The data source of this study were students of class XI IIS 1 and sociology teacher of SMAN 2 Menyuke and the results of interviews and observations. The results of this study indicate the study of sociology textbooks as a source of learning in sociology learning so that it is relevant to the learning objectives and other learning components can help improve learning efficiency and support learning goals, increase positive values in the learning process, in accordance with interactions and learning strategies that have been designed orbeing implemented. Factors that influence the development of sociology learning textbooks as a source of learning in the development of sociology learning technology. Keywords: Textbooks, Learning Resources, sociology learning